The Model of Environmental Furure City of Japan: Environmental Policy of Kitakyushu City (Journal of Oriental Studies, 2018)
The article examines the environmental problems of the city of Kitakyushu since the second halfof the twentieth century to the present, and reviews the main reforms of the four city administrationsregarding environmental policies to prevent industrial pollution and improve the state of the city’s environment.Particular attention was paid to the process of transformation from an industrially polluted cityto the transition to the environmental future city of Japan.An example of the Kitakyushu environmental future city model is considered to be a source ofvaluable data for the Republic of Kazakhstan, which implements the state program of forced industrialinnovativedevelopment and the concept of a green economy for entry into the industrial-economicdeveloped states (OECD). It is assumed that this article, from a practical point of view, plays an importantrole in improving the quality of state programs in the framework of the state environmental policypursued by the Government of the Republic of Kazakhstan.